Lina Kostenko is a culturologist, philosopher, and literary researcher - Slonovska, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
Abstract Lina Kostenko is known first and foremost as a distinguished poet, the author of the historical novels in verse ‘Marusia Churai’ and ‘Berestechko’, as well as the dramatic poem ‘Thought of Brothers Not of the Azov’, the verse drama ‘Snow The ordinary Ukrainian reader has no idea about Lina Kostenko’s scientific works, and cultural critics, philosophers, and literary specialists rarely refer to her works, i.e., ‘The Humanitarian Aura of the Nation or the Defect of the Main Mirror’, ‘Chornobyl in Doses of Historical Consciousness’, ‘Ukraine as a Victim and a Factor in the Globalization of Disasters’, and ‘The Poet Who Walked the Stairs of Giants’ in Florence’, and the lyric-epic poems ‘Scythian Odyssey’ and ‘Gypsy Muse’, which include ‘Drevlianskyi Triptych’. The reason for this unfair neglect was, first of all, that these works were not included in any of the writer’s books, even as appendices, and, except for ‘The Humanitarian Aura of the Nation or the Defect of the Main Mirror’, were not published separately in even a small number of copies. Meanwhile, the high scientific level of the above-mentioned works can be considered a reproach to the current book publishers who missed an important aspect of Lina Kostenko’s talent. It is known that Lina Kostenko, a graduate of the school, chose the Faculty of Philosophy for her admission, but the watchful totalitarian state, through the hands of the KGB, made it impossible for the talented entrant to become a student. Her father had served a term in Stalin’s prison, and the abbreviation “ЧСІР” was considered as unreliable family members of a screened, i.e. suspected, politically unreliable, ideologically hostile, perceiving his children or grandchildren as “enemies of the people”. Few people now even know that according to prisoner terminology, the prison was called the “small zone” and the USSR the “large zone”, that with the arrival of the “Brezhnev frosts” “snitching, denunciations, anonymous letters were revived again,” and that it was very unpleasant to live as a “disabled person of the fifth column” (Eleonora Solovey), in which the nationality was indicated in the questionnaires. Only in the 1990s was Lina Kostenko able to realize herself as a cultural critic, philosopher, and literary researcher, at least in some of her studies.